Uji Skrining Fitokimia Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea Batatas L) - Agus Susanto; Hardani; Sri Rahmawati (ARTERI : Jurnal Ilmu Kesehatan, 2019)
Purple sweet potato is a very familiar plant for us, and the most common is white sweet potato, purple, yellow ororange. The advantages of colored purple sweet potatoes contain anthocyanins. Anthocyanins are a secondarymetabolite of flavonoids and polyphenols that can act as antioxidants. This concentration of anthocyanins is whatcauses some kind of purple potato to have a gradient of different shades of purple. Anthocyanins provide excellenthealth effects namely as antioxidants and anticancer due to electron deficiency in its chemical structure so that it isreactive to resist free radicals. Sweet potato leaves can also be utilized as food ingredients as well as potentiallymedicines for various diseases. Purple sweet Potato (Ipomoea batatas L) is one of the agricultural commodities inIndonesia that has a number of production is quite abundant and can be used as a traditional medicine. Theproblem formulation in this study is whether purple sweet potato leaf extract (Ipomoea batatas L.) contains thechemical compounds of alkaloids, falovonoids, tannins and saponins.The purpose of this research is to know thecontent of chemical compounds in purple sweet potato leaf (Ipomoea batatas L). This research is an experimentalstudy that is by observing and conducting experimental observations of the group in various treatment conditions.The sample used in this study is the purple sweet potato leaf (Ipomoea batatas L). The results of this study showedthat the purple sweet potato leaves were positively contained.